How would 401(k) "Rothification" alter saving, retirement security, and inequality? - Vanya Horneff; Raimond Maurer; Olivia S. Mitchell (Leibniz Institute for Financial Research SAFE, 2022)
Many nations incentivize retirement saving by letting workers defer taxes on pension contributions, imposing them when retirees withdraw their funds. Using a dynamic life cycle model, we show how 'Rothification' - that is, taxing 401(k) contributions rather than payouts - alters saving, investment, consumption, and Social Security claiming patterns. We find that taxing pension contributions instead of withdrawals leads to delayed retirement, somewhat lower lifetime tax payments, and relatively small reductions in consumption. Indeed, the two tax regimes generate quite similar relative inequality metrics: the relative consumption inequality ratio under TEE is only four percent higher than in the EET case. Moreover, results indicate that the Gini measures are also strikingly similar under the EET and the TEE regimes for lifetime consumption, cash on hand, and 401(k) assets, differing by only 1-4 percent. While tax payments are higher early in life under the TEE regime, they are slightly lower in the long run. Moreover, higher EET tax payments are also accompanied by higher volatility. We therefore find few reasons for policymakers to favor either tax approach on egalitarian or revenue-enhancing grounds.
Keywords: C63; D14; G51; H31; H55; J26; 330; pensions; taxes; 401(k) plan; retirement; Social Security claiming; inequality